The exigency of ICT Resources on Teaching and Learning in South African Primary Schools - Ntsobi, Mfanelo, Patrick (My University, 2022)
The effect of Information and Communication Technology (ICT) on the teaching and learning fraterinity has globally necessitated its integration in the classroom. Nevertheless, it is important to note that the quest for Integration in individual school contexts remains an uphill task in-spite of ICT integration being a policy prerogative in a number of countries. This survey has the sole objective of unpacking how the teaching and learning process has been affected due to lack of ICT resources. By use of a simple questionnaire, the researcher made use of semi-structured interviews in order to solicit data from educators in selected South African primary schools. The interviews were transcribed manually and coded. The data analysis process was conducted by use of a thematic mode of analysis. The findindings thereof demonstrated that, due to many reasons, many schools do not make use of ICT tools in teaching and learning, as expected, and, in most cases, they do not maximise of the use of the existing resources, thus affecting the teaching and learningn processes. The reasearcher recommends that the South African Department of Basic Education (DBE) seriously takes into consideration individual school contexts when allocating ICT resources in order to try and mitigate the challenges. Stepping up the monitoring and evaluation mechanisms that are currently at play will help identify contextual challenges and the provision of assistance where necessary. Security issues also call for schools to team up with local communities to try and fight the theft and vandalization of IT resources. All these measures are meant to facilitate the preservation and use of ICT resources in the classroom for the betterment of the learning process.
Keywords: ICT integration; Information and Communication Technology; Primary education; Teaching and Learning